Penerapan Kurikulum Kerangka Kualifikasi Nasional Indonesia Pada Pembelajaran Tematik Di Sekolah Dasar - Elizabeth (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
This study aims to examine the implementation of the Indonesian National Qualifications Framework (KKNI) curriculum in thematic learning at elementary schools. The research employed a qualitative descriptive method with data collected through interviews, observations, and documentation at several elementary schools in Jakarta City. The results indicate that teachers have understood the principles of KKNI and have endeavored to integrate them into thematic learning processes, thereby enhancing student engagement and the development of 21st-century competencies. However, challenges remain in authentic assessment and administrative workload experienced by teachers. Support from principals and supervisors plays a crucial role in the successful implementation of this curriculum. This study recommends increased training for teachers and adequate resource provision to optimize the application of KKNI in thematic learning.